PERAN CRISIS MANAGEMENT INITIATIVE (CMI) DALAM MONITORING IMPLEMENTASI NOTA KESEPAHAMAN (MEMORANDUM OF UNDERSTANDING) ANTARA PEMERINTAH INDONESIA DAN GERAKAN ACEH MERDEKA (GAM) 2015-2020 - Fadhlan Nur Hakim; Sabri Ulvianda (Mediasi: Journal of International Relations, 2020)
This journal aims to explain the role of CMI in monitoring the implementation of the Memorandum of Understanding between the Government of Indonesia and GAM in 2015-2020. CMI not only helped in the negotiation process between the Indonesian government and GAM, but also in the process of peace building after the conflict With the details of the Helsinki MoU that has not been realized by the Indonesian government and there is a difference of view between the Indonesian government and GAM in interpreting the Helsinki MoU so as to cause a referendum discourse from gam to separate Aceh from Indonesia as a solution. Demanding cmi to play a role in solving the problem so that the peace that has been established can survive and continue without causing new conflict in Aceh. Therefore, this research will focus on what roles and efforts have been made by the international organization CMI in the process of monitoring the implementation of the Memorandum of Understanding between the Government of Indonesia and GAM. To answer this research the author uses the concept of mediation, using descriptive data types, and the method used is qualitative method. While the data source used is the type of primary and secondary data that wants to be proven in this thesis is the role of CMI in monitoring the implementation of the Memorandum of Understanding between RI and GAM. The results of this study show that what CMI has done is quite influential in monitoring the implementation process of the Helsinki MoU that has not been realized, namely by building effective dialogue between the two parties. Keywords : Crisis Management Initiative, Free Aceh Movement, Memorandum of Understanding, Monitoring, Implementation.